2003
DOI: 10.1007/s11886-003-0112-2
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and its effects on lipids

Abstract: Physical activity is an important component of weight control, and is widely recommended to prevent and treat obesity-related complications such as diabetes and coronary heart disease (CHD). Although the cardiovascular benefits of increased physical activity are likely multifactorial, much of the attention has been focused on the known high-density lipoprotein (HDL) cholesterol-raising properties of regular physical activity. Physical activity, however, can also reliably lower triglycerides and favorably affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 54 publications
1
31
0
1
Order By: Relevance
“…Many of these factors are known to be tightly correlated with triglyceride (11,12). Consistently, controlling for these parameters in the stepwise multivariate model demonstrated a marked attenuation of the diabetes risk associated with higher quintiles of triglyceride level.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Many of these factors are known to be tightly correlated with triglyceride (11,12). Consistently, controlling for these parameters in the stepwise multivariate model demonstrated a marked attenuation of the diabetes risk associated with higher quintiles of triglyceride level.…”
Section: Discussionmentioning
confidence: 56%
“…The level of circulating triglycerides is highly influenced by the fed-fasted state, insulin sensitivity, and lifestyle factors such as diet and physical activity (1,11,12). These make triglyceride levels a highly sensitive lifestyle biomarker at a given time point but suggest that a triglyceride determination at a single time point may inaccurately reflect long-term triglyceridemia, particularly if lifestyle modification occurred during follow-up.…”
mentioning
confidence: 99%
“…The effect of exercise on blood lipid profiles has been widely reported Szapary PO et al has shown that Physical activity raises HDL levels and decreases the concentration of very low-density lipoprotein cholesterol and triglycerides. 6,7 Long duration of practicing yoga has shown beneficial effect on cardiovascular system. A randomized controlled trial showed that diabetic patient with cardiac comorbid had performed yogic breathing program for 6 months than compared to standard treatment alone.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity has been identified as a protective factor against the occurrence and progression of many health outcomes [7,39,40]. Although the benefits of increased physical activity are likely to be multifactorial, much of the attention has been focused on the known HDL-C-raising and TG-lowering properties [41]. In this study, active PAL was found to be associated with dramatically lower risk of high TG/HDL-C ratio in both genders (OR for men, 0.69; 95% CI, 0.55-0.86; OR for women, 0.77; 95% CI, 0.62-0.96), even after adjusting for obesity and behavioral factors.…”
Section: Discussionmentioning
confidence: 99%